Assessment of the outcomes of open side-to-side choledochoduodenostomy in the management of choledocholithiasis - Barbhuiya, Eunus A.; Sarma, Santanu; Choudhury, Dhirendra N.; Vasan, Sabari S. (International Journal of Research in Medical Sciences, 2023)
Background: Gallstone disease is one of the most common digestive diseases leading to frequent hospital visits and its prevalence shows ethnic variability, with rates of approximately 10-15% in the United States and Europe. The present study aims to prospectively assess the outcomes of open side-to-side choledochoduodenostomy in the management of choledocholithiasis. Methods: This hospital-based prospective observational study was conducted in the Department of Surgery, Tezpur medical College and Hospital, Tezpur, over one year period, from July 2021 to June 2022. The study includes twenty-four patients admitted to the surgery department for bile duct stone operations. After intraoperative confirmation of the criteria, these patients underwent choledochoduodenostomy. The patients were followed for 2 months postoperatively after discharge. Results: Only a few patients had immediate postoperative complications which were managed conservatively. No patient had any evidence of retained stone, nor did they have any symptoms of cholangitis, features suggestive of the development of Sump syndrome, or any other follow-up postoperative complications. Conclusion: Open side-to-side choledochoduodenostomy should be considered a method of choice in remote areas where endoscopic facilities are lacking and in patients where cost is a factor in deciding the choice of procedure, with reduced postoperative complications like retained stones and a shorter duration of hospital stay in expert surgical hands.